Impact of the load angle on magnetic radial pressure and torque ripple of a low power PMSM with trapezoidal control. Issue 5 (27th November 2020) - Uygun, Emre; Hecquet, Michel; Tounzi, Abdelmounaïm; Depernet, Daniel; Lanfranchi, Vincent; Bruno, Serge; Tollance, Thierry
Abstract : Purpose: This paper deals with the study of the influence of the phase shift between currents and back-electromotive forces (back-EMF) on torque ripple and radial magnetic forces for a low power synchronous machine supplied with 120 degrees square-wave currents. This paper aims to establish a good compromise between efficiency, harmonics of torque and harmonics of radial forces at the origin of the electromagnetic noise. Design/methodology/approach: Based on a finite element approach, torque and magnetic pressure harmonics versus space and frequency are evaluated for different angle values. The evolutions of the different harmonics against the load angle are analyzed and compared to those of experimental measurements. Findings: Depending on the load torque, field-weakening or field-boosting can be used to reduce current harmonics contributing the most to the radial magnetic forces responsible for the noise. Besides, a compromise can be found to avoid deteriorating too much the performances of the machine, thus being suitable with an industrial application. Research limitations/implications: This study concerns low power permanent magnet synchronous machines with concentrated windings and driven with a trapezoidal control, while having sinusoidal back-EMF. Originality/value: The use of a simple mean and suitable with a large-scale manufacturing industry to reduce the identified electromagnetic-borne noise of a specific electric drive makes the originality.